A dark and mysterious place: excavations of an Iron Age settlement at Auchrannie, Brodick. Issue 1 (March 2017) - Williamson, Claire
Abstract : An extension to the accommodation of the Spa Resort at Auchrannie, Brodick, required the excavation of the remaining elements of a roundhouse and souterrain which had been partially excavated prior to the construction of the Spa Resort itself. These follow-up excavations revealed that the retained southern half of the roundhouse had been badly truncated through agricultural land use, while the souterrain passages remained largely intact, revealing evidence for timber- and stone-lined sections, and a group of overlapping pits and shallow passages at one end. While one of the passages appeared to have been infilled during, or not long after, the 2 nd century AD, the other was not backfilled until the medieval period, possibly being left open as a void until this time. Other dates also pointed to continued reuse of portions of the site on a much smaller scale throughout later periods.